2020
DOI: 10.1177/0844562120961894
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorder Symptoms Among Nurses in Canada

Abstract: Background Nurses face regular exposures to potentially psychologically traumatic events as part of their occupational responsibilities. Cumulative stress due to repeated exposure to such events is associated with poor mental health and an increased risk of developing clinically significant symptoms consistent with some mental disorders. Purpose The current study was designed to estimate rates of mental disorder symptoms among nurses in Canada and identify demographic characteristics that are associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 45 publications
5
41
1
1
Order By: Relevance
“…However, a comparison of the overall sample (composed of nurses across a variety of roles and healthcare sectors) from which this study sample was sourced, with the provincial nursing workforce demonstrated that our sample was closely representative of the nursing population in BC with respect to age, gender and professional designation [ 52 ]. Similarly, a recent national survey by the Canadian Federation of Nurses’ Union found that proportions of nurses meeting the criteria for depression (36%) and anxiety (26%) were similar to the findings of the current study, thus providing more evidence suggesting a closely representative sample [ 53 ]. Regardless of this finding, I recommend cautiously generalizing the findings beyond the study sample.…”
Section: Discussionsupporting
confidence: 82%
“…However, a comparison of the overall sample (composed of nurses across a variety of roles and healthcare sectors) from which this study sample was sourced, with the provincial nursing workforce demonstrated that our sample was closely representative of the nursing population in BC with respect to age, gender and professional designation [ 52 ]. Similarly, a recent national survey by the Canadian Federation of Nurses’ Union found that proportions of nurses meeting the criteria for depression (36%) and anxiety (26%) were similar to the findings of the current study, thus providing more evidence suggesting a closely representative sample [ 53 ]. Regardless of this finding, I recommend cautiously generalizing the findings beyond the study sample.…”
Section: Discussionsupporting
confidence: 82%
“…Nursing staff and other healthcare professionals report significant mental health challenges ( 33 ) and are also employed in correctional settings; accordingly, healthcare professionals work in the same difficult work settings as correctional officers. Healthcare staff are not typically included in groups of first responders or PSP; nevertheless, researchers have started to examine work-related mental health issues among institutional and community healthcare employees.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare staff are not typically included in groups of first responders or PSP; nevertheless, researchers have started to examine work-related mental health issues among institutional and community healthcare employees. Nurses report frequent PPTE exposures ( 33 ), with evidence that psychiatric nurses report high rates of exposure to violence and other disturbing patient behaviors ( 34 ). For example, there is evidence that most healthcare employees working in emergency departments (83.7%) report having experienced violence ( 34 ), with a mean of 28.22 such events in their careers; almost 40% of nurses, slightly more than half of direct care providers, and more than 20% of physicians report experiencing workplace violence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations